Deep Soil Water Content and Forage Production in a Tropical Agroforestry System - Sarto, Marcos Vinicius Mansano; Borges, Wander Luis Barbosa; Bassegio, Doglas; Nunes, Márcio Renato; Rice, Charles W.; Rosolem, Ciro Antonio [UNESP] (MDPI, 2022)
Agroforestry systems integrating tree and forage growth are important for maintaining soil health but may change the soil’s physical-hydric properties. Our goal was to investigate the impact of introducing Eucalyptus trees into a pasture on the soil water content throughout the soil profile. The study was conducted in a 6-year-old agroforestry system where two species of Eucalyptus were introduced into a palisade grass pasture. Soil moisture was sampled at 0.0 (planting row), 2.0, 4.0, and 6.0 m (midpoint between tree rows) from the Eucalyptus tree rows. A monoculture palisade grass pasture was used as a control. The soil water content down to a depth of 50 cm was lowest in the tree row and increased with distance from the trees. In the Eucalyptus row, the soil water content in the 0–50 cm layer was lower than in the monoculture pasture. Agroforestry systems decreased the water content in the superficial layers of the soil in the rainy months; in the dry season, the soil water contents in all layers were similar between the Eucalyptus inter-rows. In most seasons, the agroforest systems reduced the forage production close to the Eucalyptus tree rows, up to 2 m from the trees, likely due to the soil water content decrease. Overall, this study showed that in tropical regions with sandy soils, the grass and trees’ competition must be considered when establishing integrated agroforestry systems in order to maximize the advantages and benefits of the diversified agroecosystem.
Keywords: Eucalyptus; Soil moisture; Urochloa brizantha; Water uptake